Impacts of Large-Scale Expansion of Biofuels on Global Poverty and Income Distribution - Cororaton, Caesar B.; Timilsina, Govinda R. (World Bank, Washington, DC, 2012)
This paper analyzes the impact of large-scale expansion of biofuels on the global income distribution and poverty. A global computable general equilibrium model is used to simulate the effects of the expansion of biofuels on resource allocation, commodity prices, factor prices and household income. A second model based on world-wide household surveys uses these results to calculate the impacts on poverty and global income inequality. The study finds that the large-scale expansion of biofuels leads to an increase in production and prices of agricultural commodities. The increased prices would cause higher food prices, especially in developing countries. Moreover, wages of unskilled rural labor would also increase, which slows down the rural to urban migration in many developing countries. The study also shows that the effects on poverty vary across regions; it increases in South Asia and Sub-Saharan Africa, whereas it decreases in Latin America. At the global level, the expansion of biofuels increases poverty slightly.